Custom CNC milling machine - Khan, Masrur; Ahmed, Meraj Khawja; Ulay, Neaz Ahmed Abul; Sarwar, Md. Noor Islam (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.